Health-related quality of life and mental well-being of healthy and diseased persons in 8 countries: Does stringency of government response against early COVID-19 matter? - Di Long; Juanita A. Haagsma; Mathieu F. Janssen; John N. Yfantopoulos; Erica I. Lubetkin; Gouke J. Bonsel (Elsevier, 2021)
Objectives: Our study aimed to (1) assess health-related quality of life (HRQoL) and mental well-being of healthy and diseased persons in the general population during the early stage of the COVID-19 pandemic and (2) examine the relationship between HRQoL and mental well-being and individual characteristics and government response against COVID-19, as measured by the stringency index. Methods: A web-based survey was administered to a cohort of persons from the general population of eight countries: Greece, Italy, the Netherlands, Russia, South Africa, Sweden, the United Kingdom (UK) and the United States of America (US) from April 22 to May 5 and May 26 to June 1, 2020. Country-level stringency indices were adopted from the COVID-19 Government Response Tracker. Primary outcomes were HRQoL, measured using the EQ-5D-5L, and mental well-being, measured using the World Health Organization-5 Well-Being (WHO-5). Findings: 21,354 respondents were included in the study. Diseased respondents had lower EQ-5D-5L and WHO-5 scores compared to healthy respondents. Younger respondents had lower WHO-5 scores than older respondents. The stringency index had a stronger association with the EQ-5D-5L and WHO-5 among diseased respondents compared to healthy respondents. Increasing stringency was associated with an increase in EQ-5D-5L scores but a decrease in the WHO-5 index. Conclusion: The stringency of government response is inversely related to HRQoL and mental well-being with a small positive relation with HRQoL and strong negative relation with mental well-being. The magnitude of effects differed for healthy and diseased persons and by age but was most favourable for diseased and older persons.